2017
DOI: 10.1111/nmo.13275
|View full text |Cite
|
Sign up to set email alerts
|

Determining an optimal dose of linaclotide for use in Japanese patients with irritable bowel syndrome with constipation: A phase II randomized, double‐blind, placebo‐controlled study

Abstract: This study suggests that a linaclotide dose of 0.5 mg may be appropriate in Japanese patients with IBS-C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 36 publications
4
43
0
Order By: Relevance
“…By contrast, results obtained in Japan have been somewhat different. A phase II study of IBS‐C patients showed 0.5 mg per day of linaclotide to be the optimal dose . A subsequent phase III study of IBS‐C patients confirmed 0.5 mg per day of linaclotide to be effective and safe .…”
Section: Introductionmentioning
confidence: 70%
“…By contrast, results obtained in Japan have been somewhat different. A phase II study of IBS‐C patients showed 0.5 mg per day of linaclotide to be the optimal dose . A subsequent phase III study of IBS‐C patients confirmed 0.5 mg per day of linaclotide to be effective and safe .…”
Section: Introductionmentioning
confidence: 70%
“…1 Straining scored 3.9 at baseline vs 2.0 at 4 weeks in their study 2 and 3.51 (mean) ± 0.74 (SD) at baseline vs 2.62 ± 0.97 at 4 weeks in our study. 1 Note that straining was assessed on 5-point ordinate scale (1, not at all; 2, a little bit; 3, a moderate amount; 4, a great deal; and 5, an extreme amount) in our study. 1 There was no description how they evaluate the straining.…”
mentioning
confidence: 78%
“…2 In our study at 12 weeks, 88.4% patients continued linaclotide and 11.6% discontinued. 1 Despite longer trial period, overall adverse event rate was 41.1% including 17.9% diarrhea. 1 Overall adverse event rates were roughly comparable between 2 studies.…”
mentioning
confidence: 99%
See 2 more Smart Citations